Animated Video as History Learning Media: Representing Martha Christina Tiahahu in Senior High School in Malang - Maulidda Famairisa (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This study highlights the importance of using innovative learning media in education, particularly in history lessons. Using the ADDIE R&D model, the study aims to produce animated video media about Martha Christina Tiahahu for grade XI at Senior High School No. 1 in Tumpang Malang, developed with the Animaker platform. In addition, this study also evaluates the validity of the media through trials by material and media experts and measures the feasibility of the resulting media. Data were obtained through observation, interviews, and questionnaires with analysis using a Likert scale. The results show that the media validity reached 90% from media experts and 95% from material experts, with the criteria of